Combustion Rate of Solid Carbon in the Axisymmetric Stagnation Flowfield Established over a Sphere and/or a Flat Plate. (23rd April 2013) - Makino, Atsushi; Hojo, Masahiro; Shintomi, Masahito
Abstract : Carbon combustion in the forward stagnation flowfield has been examined through experimental comparisons, by conducting aerothermochemical analyses, with the surface C-O2 and C-CO2 reactions and the gas-phase CO-O2 reaction taken into account. By virtue of the generalized species-enthalpy coupling functions, close coupling of those reactions has been elucidated. Explicit combustion-rate expressions by use of the transfer number in terms of the natural logarithmic term, just like that for droplet combustion, have further been obtained for the combustion response in the limiting situations. It has been confirmed that before the establishment of CO flame, the combustion rate can fairly be represented by the expression in the frozen mode, that after its establishment by the expression in the flame-attached or flame-detached modes, and that the critical condition derived by the asymptotics can fairly predict the surface temperature for its establishment. The formulation has further been extended to include the surface C-H2 O and gas-phase H2 -O2 reactions additionally, so as to evaluate the combustion rate in humid airflow. Since those expressions are explicit and have fair accuracy, they are anticipated to make various contributions not only for qualitative/quantitative studies, but also for various aerospace applications, including propulsion with high-energy-density fuels.